Elements of Color And Lines in Lawet Dance Costumes As An Expression of The People of Kebumen Regency - PARTI, SUPARTI; Syah Naziah Nilda (Universitas Negeri Semarang, 2024)
The Lawet Dance is one of the traditional cultural heritages of Kebumen, rich in symbolism reflected through the design of its dancers' costumes. The purpose of this study is to understand how the colors in the Lawet Dance costume reflect the social, cultural, and religious values that exist in the people of Kebumen. The method used is qualitative descriptive analysis with a symbolic approach. The results of the study show that the Lawet Dance costume is not only a tool to beautify the appearance, but also a means to express the cultural values that exist in the Kebumen community. Thus, the costumes in the Lawet Dance become a symbol of culture, ethical, harmony and social meaning as an expression of the community in Kebumen Regency. For example, the use of red with bold vertical lines can reflect the courage of the people of Kebumen in maintaining their culture and traditions in the midst of changing times. Aesthetics and Harmony lies in the gently flowing lines, soothing natural colors such as green that depict the harmony between humans and nature, which is an important value in the life of the people of Kebumen.